2019
DOI: 10.1016/j.desal.2019.114126
|View full text |Cite
|
Sign up to set email alerts
|

An integrated fertilizer driven forward osmosis- renewables powered membrane distillation system for brackish water desalination: A combined experimental and theoretical approach

Abstract: An integrated fertilizer driven forward osmosis-renewables powered membrane distillation system for brackish water desalination: a combined experimental and theoretical approach. Desalination, 471(114126)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…For their part, Wafa Suwaileha et al [ 9 ], incorporated a manure-driven forward assimilation inexhaustible fueled film refining framework for bitter water desalination. This framework was used to deliver water for fertigation, recover the weakened draw arrangement, and concentrate consumable water.…”
Section: Solar-assisted Membrane Distillation Systems—state Of the Artmentioning
confidence: 99%
“…For their part, Wafa Suwaileha et al [ 9 ], incorporated a manure-driven forward assimilation inexhaustible fueled film refining framework for bitter water desalination. This framework was used to deliver water for fertigation, recover the weakened draw arrangement, and concentrate consumable water.…”
Section: Solar-assisted Membrane Distillation Systems—state Of the Artmentioning
confidence: 99%
“…Osmotic gradient processes, such as FO, have potential for agricultural irrigation. Although the individual FO process requires lower energy input and less influenced by fouling, it has some disadvantages, like the separation of the draw solution and loss of nutrients [56,57]. To separate the draw solution effectively, a post-treatment strategy is required, which increases energy consumption.…”
Section: Challenges In Membrane Technology Developmentmentioning
confidence: 99%
“…Thus, there is a drop in the osmotic pressure gradient leading to low water permeation. If using fertilizer as draw solute, the draw solution will require further dilution to meet the quality standard of irrigation water [29,56,63].…”
Section: Challenges In Membrane Technology Developmentmentioning
confidence: 99%
“…However, if a waste or free heat source is available this can be reduced considerably. For instance, Suwaileh et al (2019) demonstrated that it is feasible to provide the heating for the MD process using solar collector systems, reducing the energy footprint for a hybrid FO-MD process to a significant extent [121].…”
Section: Temperature-driven Systemsmentioning
confidence: 99%
“…However, the integrated FO-RO desalination process could possibly attain savings in energy if it was using secondary wastewater effluent as feed solution to dilute the seawater (draw solution), as discussed in the previous section [14,16]. Alternatively, the cost of the integrated FO process could be potentially reduced if the regeneration of draw solution is not required, or the energy required could be derived from low-cost or renewable sources such as solar energy or waste heat [118,121,150].…”
Section: Future Challengesmentioning
confidence: 99%